Desain Dan Animasi 3D Pesawat Terbang Menggunakan Teknik NURBS - Retnowati, Nurcahyani Dewi (SENATIK STT Adisutjipto, 2016)
Abstract— 3D computer graphics are often referred to as 3D modeling is the process of developing a mathematical representation of any three-dimensional surface of an object (either inanimate or living) via specialized software. The design of aircraft at the present time can use a variety of methods one using software Blender and NURBS technique. In the manufacture of aircraft models used animation production process flow is divided into three stages: pre-production, production and post-production. Pre-production stage such as modeling, texturing, rigging. Stage productions such as animating, lighting, rendering. In the manufacture of pre-production stage takes precision accuracy settings using NURBS techniques. While in the post-production stage that is animating, lighting and rendering is done by using video editing blender. Keywords—NURBS Technique, design, 3D animation